Structural and Thermodynamical Study of Cu-Zn-Al Shape Memory Alloys with New Compositions Produced by Hot Isostatic Press (HIP) - Karaduman, O.; Canbay, C. Aksu; Unlu, N.; Ozkul, I (Amer Inst Physics, 2019)
Hot isostatic press (HIP) is anadvanced kind of powder metallurgy production technique which preventsvaporization loss of alloying elements with low melting pointsduring melting. In this work, ternary Cu-Zn-Al shape memory alloys (SMAs) withnew chemical compositions werefabricated by using hot isostatic pressing technique,then the obtained alloys werehomogenized at 900 degrees Cand quenched in iced-brine water to surpass the formation of hypo-eutectoid precipitations and lead to the formation of beta'1 martensite phase in the alloy. Then the small specimens of the alloy were undergone through thermal and structural measurements. The thermograms obtained from differential thermal analysis measurements of the alloy byDTA instrument demonstrated the characteristic hysteresis curves and peaks of martensitic phase transformations which indicatedthe shape memory effect (SME) property exists in the alloy. The start and finish temperatures of phase transitions and some other thermodynamical parameters were determined by using the data of these thermal measurements. The structural XRD analysis made in room conditions showedthe patterns of martensitic structures. The average crystallite size of the alloyswere computed by using XRD data. The valence electron concentration (VEC) value of the alloys were also calculated, since it is a pre-conditional andhypothetical signof havingSME property. Furthermore, the effect of HIP production technique on these new Cu-Zn-Al SMAswasdiscussed.
35th International Physics Congress of the Turkish-Physical-Society (TPS) -- SEP 04-08, 2019 -- Bodrum, TURKEY
Keywords: Martensitic-Transformation; Behavior